A Note on Inclusion Properties of Weighted Orlicz Spaces - Al Azhary Masta; Ifronika -; Muhammad Taqiyuddin (IndoMS, 2020)
In this paper we present sufficient and necessary conditions for the inclusion relationbetween two weighted Orlicz spaces which complete the Osançliol result in 2014.One of the keys to prove our results is to use the norm of the characteristic functionsof the balls in R^n.